Relationships between system quality, service quality, and customer satisfaction - Mohammad Salameh, Anas Abdelsatar; Ahmad, Hartini; Zulhumadi, Faisal; Abubakar, Faruq Muhammad (Emerald Publishing Limited., 2018)
Purpose: This study aims to explore the impact of system quality dimensions, namely, ease of use, accessibility, interactivity and website innovativeness on service quality (SQ) and customer satisfaction.Design/methodology/approach: The study used a quantitative approach, by using a survey method.The unit of analysis was the individual. A total of 618 questionnaires were randomly distributed to university students and staff in Jordan.The partial least square path-modeling method was used in the estimation of causal relationships of the constructs examined in the study.Findings: The outcomes of this study showed that ease of use, interactivity and website innovativeness have significant positive relationships with the SQ. Consequently, SQ significantly influences customer satisfaction. Research limitations/implications: Limitations of this research were related to the unit of analysis, as it was conducted within the geographical region of Jordan and the university context, where the culture and level of the technological advancement may be different than other countries. Practical implications: This research can assist mobile commerce (m-commerce) service policymakers to formulate significant policies that could enhance the nature of services being rendered and thus bring greater benefits to the customers. Originality/value: This research has extended the body of knowledge on emerging trends in m-commerce innovation adoption, more specifically in the university context. Furthermore, it offers insight on the importance of m-commerce in the minds of customers, in such a way that it will bring about the intention to repeat patronage in the future.